Alat Pengumpul Buah Manggis - Abdul Rasyid Ahmad Riza,; Ahmad Adzahar Darwis,; Adam Irfan Mohd Usri,; Tuan Ibrahim, Tuan Mohd Hafeez; Suhairi Ismail,; Mohd Najib Janon,; Ghazali Kadis, (Multidisciplinary Applied Research and Innovation, 2024)
Malaysia is one of the biggest fruit exporters in the world market. Mangosteen fruit or its scientific name Garcinia Mangostana is in high demand from foreign countries such as European countries and China. Mangosteen trees in Malaysia can reach a height of around 5 meters, and trees that have reached maturity, which is 6-12 years, can produce 100 to 3000 fruits per tree. The main problem faced especially by mangosteen orchard operators is the process of picking and collecting mangosteen fruit which is still unproductive. There are various ways and tools that we have researched regarding the process of picking and collecting this mangosteen. Every tool used by farmers and small and medium entrepreneurs has several main problems, namely, not being able to pick a lot of mangosteen at one time, having low mobility, requiring high labor force, causing low productivity rates, and requiring high costs, especially the cost of labor wages. We have produced Mangosteen Collector to overcome that problem. This product can pick a lot of mangosteen fruit at one time while using little energy. In addition, this product does not have a negative impact on the environment. This product is also suitable for use by various ages from children to adults. Finally, this product is proven to save 33% more energy and time than other methods and products.